KONSTRUKSI NORMA DAN PENEGAKAN HUKUM TERHADAP PEMBUANGAN SAMPAH SEMBARANGAN DI KABUPATEN BANDUNG - Maulana Firdaus (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
The waste problem in Bandung Regency is becoming increasingly alarming along with the rising volume of waste, while the behavior of littering still often occurs and impacts the environment, health, and social life of the community. This situation reflects a discrepancy between the normative provisions in Article 5 of Law Number 18 of 2008 on Waste Management and the practice of law enforcement in the field. Therefore, this study is important to examine regulations as well as the role of law enforcement in waste management in Bandung Regency. The purpose of this study is to analyze the regulatory framework regarding obligations, prohibitions, and sanctions in efforts to prevent littering, as well as to examine the law enforcement against such violations in Bandung Regency. The research method used is a normative legal approach with secondary data collected through literature studies and analyzed using qualitative data processing techniques. Based on the research results, Bandung Regency Regional Regulation Number 1 of 2022 on Waste Management has established obligations, prohibitions, and criminal sanctions, but it has not yet regulated preventive administrative sanctions. The law enforcement orientation that focuses more on criminalization reduces the effectiveness of prevention and is not in accordance with the principle of ultimum remedium, thus conflicting with Article 5 of Law Number 18 of 2008 on Waste Management. Waste law enforcement in Bandung Regency still faces various obstacles, including the limited number of civil service investigators and a handling pattern that is more reactive than preventive. The stagnation of enforcement amid increasing waste generation has weakened the function of the law as a means of prevention and deterrence.